X-Ray Transients from the Accretion-induced Collapse of White Dwarfs - Yu, Yun-Wei; Chen, Aming; Li, Xiang-Dong (Astrophysical journal. Letters, 2019)
The accretion-induced collapse (AIC) of a white dwarf in a binary with a nondegenerate companion can sometimes lead to the formation of a rapidly rotating and highly magnetized neutron star (NS). The spin-down of this NS can drive a powerful pulsar wind (PW) and bring out some detectable multi-wavelength emissions. On the one hand, the PW can evaporate the companion in a few days to form a torus surrounding the NS. Then, due to the blockage of the PW by the torus, a reverse shock can be formed in the wind to generate intense hard X-rays. This emission component disappears in a few weeks' time, after the torus is broken down at its inner boundary and scoured into a very thin disk. On the other hand, the interaction between the PW with an AIC ejecta can lead to a termination shock of the wind, which can produce a long-lasting soft X-ray emission component. In any case, the high-energy emissions from deep inside the system can be detected only after the AIC ejecta becomes transparent for X-rays. Meanwhile, by absorbing the X-rays, the AIC ejecta can be heated effectively and generate a fast-evolving and luminous ultraviolet (UV)/optical transient. Therefore, the predicted hard and soft X-ray emissions, associated by an UV/optical transient, provide a clear observational signature for identifying AIC events in current and future observations (e.g., AT 2018cow).